Team coaching: One more clue for fostering team effectiveness - Dimas, I. D.; Rebelo, T.; Lourenco, P. R. (European Review of Applied Psychology, 2016)
Introduction and objectives: The purpose of this study was to examine the effects of team coaching (provided by the leader and by peers) on team performance and on the members` satisfaction with the team. The mediated role of peer coaching in the relationship between leader coaching and individual and team results was also analyzed.